Polyakov loop and heavy quark entropy in strong magnetic fields from holographic black hole engineering - Critelli, Renato; Rougemont, Romulo; Finazzo, Stefano I.; Noronha, Jorge (American Physical Society (APS), 2016)
We investigate the temperature and magnetic field dependence of the Polyakov loop and heavy quark entropy in a bottom-up Einstein-Maxwell-dilaton (EMD) holographic model for the strongly coupled quark-gluon plasma that quantitatively matches lattice data for the (2+1)-flavor QCD equation of state at finite magnetic field and physical quark masses. We compare the holographic EMD model results for the Polyakov loop at zero and nonzero magnetic fields and the heavy quark entropy at vanishing magnetic field with the latest lattice data available for these observables and find good agreement for temperatures T150 MeV and magnetic fields eB1 GeV2. Predictions for the behavior of the heavy quark entropy at nonzero magnetic fields are made that could be readily tested on the lattice.